Analysis of Philippine National Police Administrative Cases in Police Regional Office V - Rony Bonaobra, Rony Bonaobra; Macabeo, Manny (JPAIR Multidisciplinary Research, 2022)
The safety of the community and the degree of law and order in the state were based mainly on the efficiency of the duties and functions performed by the agent of the state. Being a public officer with state-given powers, a police officer must strictly adhere to organizational discipline. The study aims to determine the prevalent Administrative Cases in Police Regional Office 5 for CY 2019 to 2021 and identify the factors leading to the commission of administrative offenses based on the available data on the nature of cases, specific offenses, and disposition of administrative cases. It will also analyze the effects of decided administrative cases on police officers’ work performance, social relationships, and family relations. Content analysis on reliable data on the nature of cases and specific offenses and qualitative method with a phenomenological approach based on the responses of the participants were utilized to analyze the factors and effects of decided administrative cases on police officers. The study revealed that negligence, incompetency, anger management, and sexual misconduct are among the factors leading to the commission of the administrative offense. The study concludes that neglect of duty (nonfeasance) and misconduct (malfeasance) are the two (2) prevalent administrative offenses committed by a police officer. There is a need for cohesive preventive measures that enhance police discipline based on morale and spiritual upliftment, psycho-social intervention program and skill-focused activities to address the increasing number of administrative cases in PRO5.